Canadian Annual Review of Politics and Public Affairs : 1996 - Mutimer, David (Book collections on Project MUSE., 2002)
Elections dominated Canadian politics in 1996, despite there being no federal election. The fallout from Quebec's narrowly defeated referendum on sovereignty the previous year drifted across 1996's political landscape. At the same time, though barely half-way into their mandate from the 1993 Federal election, Jean Chretien's Liberal government gave every indication of gearing up for another vote in 1997. Sandwiched between these votes, 1996 saw three provincial elections, two MPs leave Ottawa to become provincial premiers, the election and subsequent resignation of a new Leader of the Opposition, and a series of federal by-elections. The by-elections were noteworthy for holding the possibility of displacing the Bloc Quebecois from its status as Official Opposition, in favour of the conservative, western-based Reform Party. Featuring essays on parliament and politics, Ottawa and the provinces, foreign affairs and defence, the Canadian Annual Review of Politics and Public Affairs provides a comprehensive account of the year's events. It is unique in its collection and presentation of the year's events, and has long been praised for its excellence.